Youth and agriculture: Key challenges and concrete solutions - Food and Agriculture Organization of the United Nations; Technical Centre for Agricultural and Rural Cooperation; International Fund for Agricultural Development (CTA / FAO / IFAD, 2014)
With older farmers less likely to adopt new technologies, the need to re-engage youth in agriculture is vital if productivity is to be increased sustainably. This publication provides real-life examples of how this can be done. It shows how tailor-made educational programmes can provide rural youth with the skills necessary to engage in farming and adopt environmentally friendly production methods. Clearly laid out, with numerous case studies, photos and examples, topics covered also include accessing land and finance, connecting to markets and ‘green’ jobs.